Cooperative Lane-change on the Main-line of Highway in a Connected Vehicle Environment. Issue 1 (May 2021) - Lin, Peiqun; Chen, Chen; Huang, Xin; Ran, Bin
Abstract: The main-line lane-change (LC) and ramp LC are critical factors which decrease the mobility and safety of the transportation system. Connected Vehicle Technologies (CVTs) bring promising foundations for both types of LC to improve the traffic efficiency and reduce the crash risks by using real-time communication and systematic operation. Based on an 5G communication architecture, this paper proposes a novel CVT-based cooperative LC method which can be used for advanced traffic management to enhance the transport service. In the proposed approach, several Roadside Units (RSUs) are set up on the main-line of a highway to communicate with and manage connected client vehicles (CVs) for traffic flow smoothing. A mathematical model is developed to address the systematic maneuver of vehicles' LC in the connected vehicle environment (CVE), and its solution algorithm is also proposed. In order to assess the proposed method, a simulation test-bed is developed using VISSIM COM, and a typical highway network is employed as the study case. The simulation results illustrate that the proposed method can increase 20.7% of traffic capacity in a two-lane highway. And when it is applied in dense traffic environment, it can reduce more than 90% of travel delay, more than 75% of maximum queue length, and more than 10% of fuel consumption and gas emission. Moreover, sensitivity analysis shows that the market penetration of CVT is a key factor that affects the result of CVT-based cooperative LC.